Role of diagnostic laparoscopy in chronic pelvic pain - Bhatia, Pushpa; Gupta, Pratiksha; Mor, Devika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Laparoscopy in chronic pelvic pain can reveal findings that cannot be detected clinically, so it can be treated and diagnosed at same sitting. This study was undertaken to evaluate role of diagnostic laparoscopy in chronic pelvic pain. Methods: It was a prospective study conducted at department of Obstetrics and Gynecology, ESI PGIMSR, Basaidarapur, New Delhi. The study was carried out from 2012- 2014. Total 110 cases were enrolled. 55 cases who had been suffering from chronic pelvic pain for ≥6 months were taken as study group (A). 55 cases without any symptoms that underwent laparoscopic sterilization were taken as control group (B). Results were statistically analyzed using Karl Pearson's correlation coefficient. Results: Chronic pelvic pain whereas on laparoscopy normal finding were seen only in 25.45% cases. This difference was found to be statistically significance (P value 0.04). Normal findings were seen in 60% cases of chronic pelvic pain on USG as compared to 25.14% cases on laparoscopy was statistically significant .( p value <0.05.) Conclusions: Laparoscopy is a gold standard tool in evaluation of women with chronic pelvic pain, because diagnosis and often treatment can be accomplished in one sitting, without subjecting them to exploratory laparotomy.